Prevalence of Intestinal Parasites among Nomads in Hong Local Government Area, Adamawa State, Nigeria - Altajiri Innocent; Jesse Daniel; Hussaini Nalle (African Multidisciplinary Journal of Sciences and Artificial Intelligence, 2026)
Intestinal helminth infections remain a major public health concern in tropical regions, with nomadic populations such as the Fulani in Adamawa State, Nigeria, facing heightened risk due to limited access to sanitation, clean water, and health education. This study assessed the prevalence and associated risk factors of intestinal helminth infections among two nomadic Fulani settlements in Hong Local Government Area (LGA). A community-based cross-sectional study was conducted from July to September 2025 in Warchirashan and Fa’a Fulani settlements. Stool samples (n = 220) were collected from randomly selected participants and analyzed using the concentration method, while socio-demographic data and risk factors for soil-transmitted helminths were obtained via structured questionnaires. Data were analyzed using SPSS v26.0, and associations between infection status and risk factors were assessed using Chi-square tests (p < 0.05). The overall prevalence of intestinal helminth infections was 34.5%, with similar rates in Warchirashan (33.6%) and Fa’a (35.5%). The most prevalent parasites were Ascaris lumbricoides (11.4%), Trichuris trichiura (12.3%), and Schistosoma mansoni (11.4%). Single-species infections predominated, although polyparasitism occurred in 33–38% of infected individuals. Age-specific prevalence was highest among 18–30-year-olds, consistent with greater occupational exposure, and infection rates were higher in males than females (39.6% vs 25.9%), although this difference was not statistically significant. Significant risk factors included source of drinking water, open/bush defecation, and inconsistent handwashing practices. The study concludes that a moderate prevalence of intestinal helminth infections persists among nomadic Fulani communities in Hong LGA, driven by environmental and behavioral determinants, and recommends integrated control strategies—combining improved sanitation, safe water access, regular deworming, and targeted health education—to reduce the infection burden across all age groups.